Experiences of principalship: a case study of two female leaders of suburban high schools in Gauteng - Chiramba, Otilia Fortunate (My University, 2016)
This study explores the experiences of two women principals in leading suburban co-educational high schools in Gauteng province, South Africa. It sought to explore and understand the experiences of two women principals and their leadership roles through the consideration of their challenges, their successes and their leadership styles as demonstrated in their school contexts. Gender and leadership is an area which remains under-researched in both the South African and the national and international educational leadership fields (Faulkner, 2015; Moorosi, 2010 & 2012). Also in South Africa there is very little knowledge of the experiences of women leading suburban co-educational high schools formerly known as Model C schools (Lumby & Heystek, 2011). This context is particularly interesting and important considering the dramatic change in demography of these schools after 1994, which impacts upon how women principals, in particular, experience and lead these diverse schools and their very diverse communities. As the schools now have heterogeneous ethnic and cultural populations, principals face many different challenges in leadership. In a very patriarchal and traditional culture, which typifies South Africa, it was considered an important aspect of the research to understand the experiences of women specific to these under-researched school contexts. The research methodology chosen as the most appropriate is a qualitative, interpretivist approach which uses a case study. The two high schools in the case study were purposefully sampled because they were led by women and they were former Model C schools in Gauteng, to the west and north, which under the apartheid regime served only white learners and communities in former affluent white suburban areas. The participants in this study were the two women principals of the two suburban schools. The research instruments chosen were a semi structured questionnaire, loosely based on Coleman’s questionnaire from her study of UK head teachers (2001), and follow-up probing interviews to gain more in depth responses to key areas of interest. The research was underpinned by a theoretical framework that contends that context plays a significant role in the two women’s experiences and how this might impact upon challenges to their leadership as women, (Christie & Lingard, 2001). Cubillo and Brown (2011) posited in their research that context is critical to women’s experiences of leadership, even more than is the case for male leaders. Evidence from the data collected and analysed in addressing the research questions shows that the two women principals were negatively affected by entrenched patriarchal attitudes within the communities they served. Contexts of former Model C schools played a pivotal role in the two women’s experiences as they employed the leadership styles they considered as the ones that best fitted the situations imposed by diverse ethnic and cultural communities. The misconception about former Model C schools, as still being sites of affluence and privilege, also contributed to their challenges, given the demographic changes that contradict this assumption. Despite these challenges, the two women remained strong with the determination to lead successfully ‘against the odds’ (Coleman, 2001). Family support, work experience, qualifications, confidence and their leadership styles also contributed to their success. This study recommended the need for further research through a longitudinal and wide ranging study of women’s experiences of leadership and specifically on the nature of leadership in these under-researched co-educational former Model C high schools. Keywords Gender and leadership, Principalship, South African High Schools, Discrimination, Patriarchy, Glass Ceilings and Walls,
Research Report submitted to the School of Education, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the Degree of Master of Education. February 2016
Keywords: Women school principals--South Africa; High school principals--South Africa; Educational leadership